ANALYSIS OF TEACHER READINESS IN IMPLEMENTING THE INDEPENDENT LEARNING CURRICULUM AT SENIOR HIGH SCHOOL 1 SAMATURU - Ismayanti, Ismayanti (Geographica: Science and Education Journal, 2024)
This study aims to analyze teacher readiness in implementing the independent learning curriculum at SMA Negeri 1 Samaturu. This is motivated by the change in curriculum at SMA Negeri 1 Samaturu which makes teachers have to carry out the learning process on the independent curriculum implemented at school. Even though there is already an independent learning platform, teachers still need adjustments in implementing an independent curriculum such as learning strategies, facilities and infrastructure to support the teaching and learning process, the teaching materials used also still follow the steps in the previous curriculum learning so that teachers need to prepare themselves during the teaching and learning process. The type of research used in this research is descriptive research with a qualitative approach. The instruments used were observation sheets and interview guidelines. This research was conducted at SMA Negeri 1 Samaturu with 20 teachers as the research subjects. Data collection techniques in this study used observation, interview, and documentation techniques. The data analysis used is qualitative data analysis technique according to Miles and Huberman. Based on the results of the study, it can be seen from the five predetermined indicators, namely the teacher's understanding of the structure of the independent curriculum, the teacher's readiness in lesson planning, the teacher's readiness in the learning process, the readiness of the teaching module in lesson planning and the readiness of learning assessment in general, it can be concluded that they are ready, this is supported by the fact that all SMA Negeri 1 Samaturu teachers have participated in training on the implementation of the independent curriculum, so they understand the policies in implementing the independent curriculum, besides that all teachers already have and are able to compile teaching tools in the independent curriculum.